2022
DOI: 10.1155/2022/2949297
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] The Prevention and Control Mechanism of Sports Risks in Colleges and Universities under the Background of the Integration of Sports and Education

Abstract: Based on the theme of sports risk prevention and control in colleges and universities, the connotation and classification of sports risk in colleges and universities are recognized and screened, the theoretical basis of sports risk prevention and control in colleges and universities is interpreted, and the needs of sports risk prevention and control in colleges and universities are analyzed. On the basis of questionnaire and expert interview, the analytic method is used to construct the evaluation index system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Azimxo'jayevich, I et al put forward the reform of the sports system by analyzing the education mode of sports and sports organizations as well as the training problem and believe that the reform of sports physique can play a certain role in promoting the cultivation of sports talents [11]. Lingmin, W et al believe that the prevention and control of risks of sports in colleges and universities is a very necessary thing, through the construction of a sports risk evaluation index system to provide data guidance for sports management in colleges and universities to a certain extent to promote the management and cultivation of sports talents [12]. Goodman, A et al believe that the use of training clinical programs is also a part of sports.…”
Section: Introductionmentioning
confidence: 99%
“…Azimxo'jayevich, I et al put forward the reform of the sports system by analyzing the education mode of sports and sports organizations as well as the training problem and believe that the reform of sports physique can play a certain role in promoting the cultivation of sports talents [11]. Lingmin, W et al believe that the prevention and control of risks of sports in colleges and universities is a very necessary thing, through the construction of a sports risk evaluation index system to provide data guidance for sports management in colleges and universities to a certain extent to promote the management and cultivation of sports talents [12]. Goodman, A et al believe that the use of training clinical programs is also a part of sports.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%